Gratitude in Early Adulthood Women Survivors of Sexual Harassment - Hasbyallah, Dicky; Rahmasari, Diana (Character Jurnal Penelitian Psikologi, 2023)
This study aims to examine the processes, factors, and benefits of gratitude in early adulthood women who are survivors of sexual harassment. Early adulthood is the age when individuals experience the transition from adolescence to adulthood. This age is a critical period, especially at the age of 18-20 years. Age 18-20 years is a period when individuals experience emotional tension because they are faced with changes in responsibilities and different developmental tasks. Failure to overcome stressful live events due to harassment will have a negative impact on individuals. This research is important because gratitude is an important aspect for early adult women to reduce negative emotions from the impact of harassment. This research uses a qualitative approach with a case study method. Data were obtained through semi-structured interviews and analyzed through thematic analysis techniques. Participants in this study were three young adult women who experienced unwanted sexual attention. By referring to the gratitude aspect developed by Watkins, the three participants were able to form gratitude. Gratitude is achieved by several processes involving psychological, cognitive, and social aspects. Gratitude can increase awareness, happiness, and form self-acceptance. Factors that support the formation of gratitude are self-motivation and support from friends.